Analisis Perilaku Gasab dalam Kehidupan Sehari-hari Santriwati Kelas 1 Tsanawiyah di Pondok Pesantren Miftahul Ulum Jakarta Selatan - Yokha Latief Ramadhan; Allaya Sabina Dahuri; Sururin Sururin (Journal on Education, 2023)
Gasab is a behavior in the form of using other people's belongings without the permission of the owner first. Gasab, as a violation of norms in Islamic boarding schools, occurs continuously. As a place for students to study and study religion, Islamic boarding schools have fostered a high sense of togetherness and solidarity in the pattern of relationships between students, which is the cause of gasab behavior among students. The items that are raped are items that are often used in the daily lives of students, such as shoes, sandals, dippers, clothes, and other items.